Comparison of the accuracy of multiparametric magnetic resonance imaging (mpMRI) results with the final pathology findings for radical prostatectomy specimens in the detection of prostate cancer. Issue 2 (19th June 2018) - Lee, Chan Ho; Ku, Ja Yoon; Park, Won Young; Lee, Nam Kyung; Ha, Hong Koo
Abstract: Aims: To assess the accuracy of multiparametric magnetic resonance imaging (mpMRI), used in conjunction with the Prostrate Imaging Reporting and Data System (PI‐RADS), version 2, in the detection of prostate cancer (PCa), and to determine the extent of the efficacy of mpMRI as a screening test in biopsy‐naïve patients. Methods: Retrospective analysis was conducted in 107 patients who underwent mpMRI prior to radical prostatectomy (RP) at a single institution. The mpMRI findings were reassessed using PI‐RADS, version 2. A comparison was made between the histological findings for the RP specimens and the mpMRI results. Results: Unique histologically confirmed PCa foci (237) were identified in 107 patients. Overall, mpMRI sensitivity of 46% was found for PCa detection (110/237). The sensitivity, specificity and negative predictive value of mpMRI was 75.5%, 77.0% and 79.8%, respectively, for clinically significant cancer, and 75.7%, 77.7% and 79.5%, for pathological index tumors. A moderate and significant correlation was observed between a high PI‐RADS score and a high pathological grade, tumor volume, index tumor status and clinically significant cancer status (all, P  < 0.001, respectively). Pathological tumor volume was a significant predictor of PCa detection using mpMRI according to multivariate analysis. Using a cut‐off value of 0.89 cc, the sensitivity and specificity of mpMRI for PCa detection were 0.87 and 0.65, respectively. Conclusion: The mpMRI, used in conjunction with PI‐RADS, was useful in detecting PCa and in predicting tumor aggressiveness. However, the detection of 20% of clinically significant cancer was missed using mpMRI. Thus, its inclusion in a triage test should be limited to selected biopsy‐naïve patients.